Using encapsulatedNannochloropsis oculatain white chocolate as coloring agent - Polat, Derya Genc; Durmaz, Yasar; Konar, Nevzat; Toker, Omer Said; Palabiyik, Ibrahim; Tasan, Murat (SPRINGER, 2020)
Colored chocolate products have gained importance in recent years. This increases the importance of identifying potential natural colorants for chocolate technology. In this study,Nannochloropsis oculatamicroalgae which were grown by using tubular photobioreactor in two different forms (spray-dried and encapsulated by using a spray dryer and maltodextrin (50%)), were used in white chocolate composition (0.00-0.75 g) as a coloring agent. The color stability (Delta E) values for all sample groups were determined below the visibility level of 3.0 under accelerated shelf life conditions (25 degrees C/70% RH) for 28 days. The water activity, moisture and ash content, hardness, yield stress, plastic viscosity, and melting properties of white chocolate samples showed no significant differences (P > 0.05) and the other quality characteristics were found to be acceptable. The chlorophyll-acontent of white chocolate samples was between 9.60-22.9 mu g g(-1). It was found that the sensory properties of the samples as appearance, texture, melting in the mouth, and odor were not affected by level of microalgae use (P > 0.05). However, it was noteworthy that there was a decrease in taste and overall acceptability according to usage level of dried and encapsulated microalgae (P < 0.05). As a result, it was determined that spray-drying technique is preferred for use of microalgae in chocolate composition.
Keywords: Chocolate; Microalgae; Color; Nannochloropsis oculata; Pigment; RHEOLOGICAL PROPERTIES; SENSORY PROPERTIES; DARK CHOCOLATE; MILK CHOCOLATE; COMPOUND CHOCOLATE; BULKING AGENTS; ANTIOXIDANT; SWEETENERS; ENRICHMENT; Biotechnology & Applied Microbiology; Marine & Freshwater Biology